Pakistan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
This Selected Issues paper analyzes Pakistan's tax reform and revenue performance. The paper assesses the nature and magnitude of Pakistan's actual twin debt problem in a historical context, and reviews the policy options. The study highlights the factors explaining the recent stagnation in merchandise exports, and analyzes the country's export performance with regard to the linkages between performance and the structure of exports. The paper reviews a survey of poverty in Pakistan, and also provides a statistical appendix report of the country.